El Excentrico, 1963-08-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
August 5, 1963 [5 de Agosto de 1963]. Ano 13, No 20. Cover has a photo of eight candidates for the 16th of September Fiesta. Picture from left to right are, Gloria Rosas, Elsie Navarrete, Ella Calderon, Yolanda Guerra, Mary Anna Paiz, Trini Gutierrez, Mary Guerrero, and Pauline Balder.